A facile synthesis of a highly water-soluble and selective fluorescent sensor towards zinc ions derived from β-cyclodextrin based on an unexpected sensing process. Issue 122 (24th November 2015) - Liu, Zengchen; Yang, Weijie; Li, Yanxia; Tian, Fengshou; Zhu, Wenping
Abstract : A highly selective and sensitive fluorescent sensor for Zn 2+ derived from a β-cyclodextrin derivate was fabricated. Through fluorescence micrograph experiments, the sensor showed an excellent image effect on onion epidermal cells. Abstract : A highly water-soluble and sensitive fluorescent sensor derived from β-cyclodextrin with relatively lower toxicity was synthesized. The fluorescent sensor exhibited spherical morphology under SEM observation. By the fluorescence behavior towards several metal ions, the sensor showed high selectivity and sensitivity for Zn 2+ over other commonly co-existent metal ions in a pure water environment (pH = 7.2). Moreover, the large binding constant (2.55 × 10 13 M −1 ) between Zn 2+ and the fluorescent sensor was calculated in a pure water media. The fluorescent microscope images of onion epidermal cells proved that the water-soluble sensor showed a high ability for cell permeability. In addition, a chelating induced fluorescence enhancement (CIFE) and photoinduced electron transfer (PET) sensing mechanism was concluded according to the fluorescence behavior. The fluorescent sensor in a pure water media effectively enhanced the application value of the fluorescent sensor for the tracking and detection of Zn 2+ .